Comparison of the effects of basic movement training and gymnastic programs on gross motor skills in children - KİRİŞCİ, İLKER (My University, 2023)
The aim of this study is to compare the effects of basic movement training and gymnastics programs on gross motor skills in 5-6 year old children. 18 female and 12 male students, who were registered to a sports facility in Bayrampaşa district and did not have any previous sports activities, participated voluntarily and were divided into two groups, each consisting of 15 students. Basic movement training was given to the first group and gymnastics training was given to the second group. Gross motor skill test was used to collect the data. The suitability of the research was approved with the decision numbered 2022-10-15 of the Ethics Committee of Istanbul Gelisim University Rectorate. Results were made using SPSS 25.0 package program. Obtained data were analyzed by t-test (independent samples t-test) in dependent groups. When the in-group measurement values of the experimental groups were examined, a statistically significant difference was found between the pre-test and post-test comparisons of standing long jump, static balance, dynamic balance and quickness parameters (p<0.05). In the pre-test and post-test comparison between the two experimental groups, a significant difference was found in the static balance parameter (p<0.05). As a result, it has been determined that gymnastics and basic movement training exercises have a positive effect on the parameters of standing long jump, dynamic balance, static balance and quickness. The duration of the research was arranged as 6 weeks. If the period is extended to 10-12 weeks, progressive changes in children can be revealed more clearly. At the same time, it is recommended to increase the number of participants and arrange them as three days a week instead of two.
Keywords: Movement education; child; gymnastics; motor